Interpreting modernity : essays on the work of Charles Taylor - Weinstock, Daniel M.; Levy, Jacob T., 1971-; Maclure, Jocelyn, 1973- (McGill-Queen's University Press, 2020)
"There are very few philosophical questions to which Charles Taylor has not devoted his attention. His work has made powerful contributions to our understanding of action, language, and mind. He has had a lasting impact on our understanding of the way in which the social sciences should be practiced, opposing an interpretive stance to dominant positivist methodologies. His powerful critiques of atomist versions of liberalism has redefined the agenda of political philosophers. He has, moreover, produced prodigious intellectual histories aiming to excavate the origins of the way in which we have construed the modern self, and of the complex intellectual and spiritual trajectories that have culminated in modern secularism. Despite the apparent diversity of his work, it is driven by a unified vision. Throughout his writings, Charles Taylor has sought to oppose reductive conceptions of the human and of human societies that were thought by empiricist and positivist thinkers from Hume to Skinner and beyond to lend rigour to the human sciences. In its place, Taylor has articulated a vision of humans as interpretive beings, who can be understood neither individually nor collectively without adverting to the fundamental goods and values through which they make sense of their lives. The contributors to this volume, all of them distinguished philosophers and social theorists in their own rights, offer critical assessments of the full range of Taylor's writings. Taken together, they provide the reader with an unrivalled perspective on the full extent of Charles Taylor's contribution to modern philosophy. "--